ACCOUNTING AND VALUATION OF FOREIGN ECONOMIC ACTIVITY OF RUSSIAN REGIONS - Natalya Adintsova; Elena Zhuravleva (Вестник Северо-Кавказского федерального университета, 2022)
The factors affecting the organization of accounting and the characteristic indicators of assessment of foreign economic activity of subjects of the Russian Federation. As well as the technique of calculation of some indicators of assessment offoreign economic activity of the enterprises of the region. Certain difficulties in the implementation of export operations associated with separate VAT. Separate VAT accounting can lead to the taxable and non-taxable operations, or when using different tax rates.